Influence of oxide layers on optical properties of copper in a wide spectral range - Filipov, Y.V.; Staschuk, V.S.; Poperenko, L.V. (Functional Materials, 2005)
Optical properties of flawless bulk copper sample has been studied based on spectroel-lipsometry measurements in a wide spectral interval (Av = 0.18 to 4.87 eV) at various angles of light incidence. The main characteristics of electronic subsystem of this metal and values of main energy intervals in a band structure have been calculated. Taking into consideration influence of the surface oxide layer.